Irrigation and nutritional management in clonal minigardens of Tectona grandis (Linn. F) in the southern zone of Costa Rica - Calderón-Ureña, Fiorella (2019)
The forestry nutrition is a current development topic into in the nursery stages and also in plantations. In some cases there is evidence of nutrition deficiencies from the clonal minigardens, which are one of the initial stages in a clonal nursery. In a clonal minigarden with Tectona grandis (Linn. F) the irrigation system and a treatment application were evaluated by mixing fertilizer doses with varied irrigation criteria to apply the fertigation technique. The Christiansen and distribution uniformity coefficients were determined for the irrigation system. In addition to the treatments, the weekly factor was also used to evaluate the behavior of teak mother plants considering the sprouts harvest. The irrigation system showed results of its uniformity that placed it in an inacceptable level. Regarding the variable measures (diameter, height and number of sprouts) there weren´t significant difference (p ≤ 0.05) between treatments but if were between weeks. In this proyect it is concluded that although there weren´t significant difference between treatments, the costs for using salts as fertilizer are considerably lower.